Guard Cells Integrate Light and Temperature Signals to Control Stomatal Aperture - Kostaki, Kalliopi-Ioanna (Plant Physiol, 2020)
High temperature promotes guard cell expansion, which opens stomatal pores to facilitate leaf cooling. How the high-temperature signal is perceived and transmitted to regulate stomatal aperture is, however, unknown. Here, we used a reverse-genetics approach to understand high temperature-mediated stomatal opening in Arabidopsis (Arabidopsis thaliana). Our findings reveal that high temperature-induced guard cell movement requires components involved in blue light-mediated stomatal opening, suggesting cross talk between light and temperature signaling pathways. The molecular players involved include phototropin photoreceptors, plasma membrane H(+)-ATPases, and multiple members of the 14-3-3 protein family. We further show that phototropin-deficient mutants display impaired rosette evapotranspiration and leaf cooling at high temperatures. Blocking the interaction of 14-3-3 proteins with their client proteins severely impairs high temperature-induced stomatal opening but has no effect on the induction of heat-sensitive guard cell transcripts, supporting the existence of an additional intracellular high-temperature response pathway in plants.